Character Education Perspective of Contemporary Figures - Fadhlurrahman Fadhlurrahman; Hatib (Educan : Jurnal Pendidikan Islam, 2023)
Character Education is a milestone in Indonesian education. One indicator of the quality of Indonesian education is seen in the student's character. The purpose of this study seeks to describe and analyze the perspectives of contemporary figures on character education. The methodology used in this scientific work is library research with a description-analysis approach and data validation with in-depth primary sources. The results of this study reveal that all contemporary figures think that character education is crucial and must be implemented immediately, either through the system or school regulations. This character education will prevent moral degradation in this era of disruption. What is novel in this study is the philosophical view of character education according to contemporary Indonesian figures.